The adamant : poems - Ruefle, Mary, 1952- (Iowa poetry prize., 1989)
This early book in Mary Ruefle's poetic career makes it clear that her main preoccupation is to make it new while following her bliss: that is, her early work is utterly different from her middle and later books. Wherever she goes next is departure from what's she's already done, and an arrival into something new. She is always discovering something fresh in her work.Whichever book of hers I pick up, whether it's the work of a poet just setting out, or any one of those ten volumes she has written along the way, the combination of range and breadth, along with depth, is phenomenal. It's a rare.